Catalog of Introduced Molluscs of Eastern North America (North of Mexico) - Dee S. Dundee (Hello World!, 1974)
The intent of this work is to provide a comprehensive list of the introduced land and freshwater mollusks of North America north of Mexico and east of the Rocky Mountains. This will include existing colonies verified by recent collecting, literature records wherein a species was reported to be established at one time (some may no longer exist if they did not become well established), private and museum collections and individual communications. Also, for comparative interest the interceptions of these mollusks by United States Department of Agriculture are listed.